1st. Olympic Council of Asia Sports Congress Kuwait City, Kuwait 12-14 March 2009 - Krasilshchikov, Oleksandr (Pusat Pengajian Sains Kesihatan, 2009)
Beijing Olympics were destined to become crucial point in the history of the development of sports in Asia not only because China was widely projected as overall winner in the coming Olympics, but also because other Asian countries emerged among top powers in the Olympic movement. Since Atlanta 1996 Olympics the presence of Asian countries was felt in a quick progressing manner and was obviously speeding further up from one Olympics to another. Sydney Olympics happened to be by then the best-ever showing by Asia. Asian teams had captured 50 gold medals (15.8 % of the total) compared with 31 gold medals at the 1996 Atlanta Olympics. China, with 28 gold medals, moved up from fourth ranked in Atlanta to No 3 behind only the United States (with 39 gold medals}, and Russia (with 32). Japan shot up from 23rd spot to 15th, while South Korea ended up in quite prestigious 12th position. Other Asian countries also reached new heights at Sydney. Vietnam won its first ever Olympic medal and the bronze of Sri Lanka was the first medal for the country in 52 years. Indonesia, ranked 37th, emerged as the top South East Asian team. Athletes from Taiwan, North Korea, India and Thailand also got their way to the podiums. In four years time, Asian countries led by China supported by tremendously improved Japan and South Korea reached the new performance level at Athens 2004 Games.